Transforming Transport Solutions [Schwerpunktthema]. - (:unkn) unknown (Trialog Publishers, 2020)
Die Beiträge der special edition 2 im Einzelnen: H. Fromm / P. Jochem: A study on free-floating carsharing in Europe (S. 28-30); F. Straube / B. Nitsche: Heading into “The New Normal”. Potential development paths of international logistics networks in the wake of the Coronavirus pandemic (S. 31-35); P. Papaghiannakis: The Perpignan-Figueras high-speed line. A great European project that arrived in the middle of a crisis and in an immature environment (S. 36-40); A. Beer: New mobility concepts for rural areas. Lessons learnt in the European cooperation project “Peripheral Access” (S. 41-43); Innovative transport systems. Random selection of European Friedrich-List-Prize submissions (S. 44-61): A. Gunter: Electrification of road freight transport. Potentials and challenges of catenary guided systems for distribution system operators (S. 44-47); M. Loidolt: Costs of operational hindrance. Reduction of railway system costs by means of a holistic approach (S. 48-50); I. Cvitić: Network traffic anomaly detection in IoT (S. 50-52); D. Földes: Innovative transport systems and mobility services (S. 53-55); T. Kerényi: Creation of mobility packages based on the MaaS concept (S. 55-58); J. Weber et al.: Non-probability recruitment strategies for innovative smartphone-based travel surveys (S. 58-61); M. Gather / C. Hille: Environmental effects of the Covid-19 lockdown. The example of an EU online convention (S. 62-64).
International Transportation, Special edition 2
Keywords: Verkehrswende; Mobilitätskonzept; Innovation; Logistik; Hochgeschwindigkeitsstrecke; Ländlicher Raum; Verkehrsdienstleistung; Straßengüterverkehr; Carsharing; Periphere Region; Ländlicher Raum; Verkehrsforschung; Wettbewerbsbeitrag; Forschungsarbeit; Verkehrsinfrastruktur; Verkehrskonzept